Radioisotope excited EDXRF analysis of sediment core samples from the southern part of the Black Sea - Bassari, A.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (My University, 2001)
In all 43 sediment samples were collected as gravity cores in depth from 70 to 150 cm, from the 20 sampling sites of the continental slope of the southern part of the Black Sea, during 1978. The samples were quantitatively analyzed by radioisotope excited energy dispersive X-ray fluorescence spectrometry (EDXRF) using fundamental parameter technique (FTP). The investigated sediment samples were the organic rich-mud components of the core samples, which were known as rich in metals. The metal concentration ranges were as follows: Ca (3.1-12.9%), Ti (1000-2000 μg/g), V (40-150 μg/g), Cr (30-200 μg/g), Mn (200-1500 μg/g), Ni (25-100 μg/g), Cu (20-70 μg/g), Zn (20-50 μg/g), Br (15-670 μg/g), Rb (5-90 μg/g), Sr (80-700 μg/g), Y (10-20 μg/g), Mo (10-111 μg/g), Zr (20-190 μg/g), Cd (<1-5 μg/g), Sb (<1-5 μg/g), I (10-430 μg/g), Ba (100-1650 μg/g), La (5-18 μg/g), Ce (12-38 μg/g) and Nd (6-17 μg/g). The sediment cores systematically collected in 1978 by Mineral Research and Exploration Institute of Turkey (MTA) are the oldest available sediment samples from the Turkish coastline of the Black Sea. Therefore, the results may be used as references for monitoring possible future metal pollution.
Keywords: INORGANIC; ORGANIC; PHYSICAL AND ANALYTICAL CHEMISTRY (S37); ENVIRONMENTAL SCIENCES (S54)